2003
DOI: 10.1126/science.1085710
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Selective Advantage of Pathogenic FGFR2 Mutations in the Male Germ Line

Abstract: Observed mutation rates in humans appear higher in male than female gametes and often increase with paternal age. This bias, usually attributed to the accumulation of replication errors or inefficient repair processes, has been difficult to study directly. Here, we describe a sensitive method to quantify substitutions at nucleotide 755 of the fibroblast growth factor receptor 2 (FGFR2) gene in sperm. Although substitution levels increase with age, we show that even high levels originate from infrequent mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
284
5
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(305 citation statements)
references
References 20 publications
7
284
5
3
Order By: Relevance
“…Fgf2 amplifies the effects of GDNF, while the addition of other growth factors does not further stimulate proliferation, indicating that the combination Gdnf/Fgf2 is the limiting factor. Fgfr2 is also expressed by human spermatogonial stem cells and may play a role analogous to Ret in regulating their clonal expansion and fate (Goriely et al, 2003). Gdnf and Fgf2 are part of a cocktail of factors used recently by several investigators to establish long-term cultures of gonocytes and spermatogonial stem cells (Kanatsu-Shinohara et al, 2003;Kubota et al, 2004b).…”
Section: Other Gdnf Target Moleculesmentioning
confidence: 99%
“…Fgf2 amplifies the effects of GDNF, while the addition of other growth factors does not further stimulate proliferation, indicating that the combination Gdnf/Fgf2 is the limiting factor. Fgfr2 is also expressed by human spermatogonial stem cells and may play a role analogous to Ret in regulating their clonal expansion and fate (Goriely et al, 2003). Gdnf and Fgf2 are part of a cocktail of factors used recently by several investigators to establish long-term cultures of gonocytes and spermatogonial stem cells (Kanatsu-Shinohara et al, 2003;Kubota et al, 2004b).…”
Section: Other Gdnf Target Moleculesmentioning
confidence: 99%
“…However, the paternal origin of the mutation and advanced paternal age associated with achondroplasia suggested that a germline selection model in which mutant spermatogonial stem cells have a proliferative or survival advantage over unmutated cells could better account for the observed paternal age effect (Dakouane Giudicelli et al 2008;Shinde et al 2013). This paternal age effect also occurs with gainof-function mutations in FGFR2 that cause craniosynostosis syndromes (Goriely et al 2003(Goriely et al , 2005Goriely and Wilkie 2012).…”
Section: Chondrodysplasia Syndromesmentioning
confidence: 99%
“…Direct measurements [4][5][6] in normal sperm and testes are laborious, and segregation of normal and mutant alleles in sperm of heterozygotes for PAE mutations is not expected to deviate from 50:50. Recently, the first direct study of new mutations in the human germ line, obtained by whole-genome sequencing Figure 1 | Illustrative depiction of how enrichment of functionally significant paternal age effect mutations could occur.…”
mentioning
confidence: 99%